From boom to bust: how different has microfinance been from traditional banking? - Charlotte Wagner (Frankfurt School of Finance & Management, 2010)
This paper presents an in-depth analysis of developments in the microfinance sector before and after the Lehman Brothers collapse in 2008 by comparing them with developments in traditional banking sectors of emerging market economies and developing countries. The findings indicate that microfinance has been part of the same credit boom observed in the traditional banking sector. Moreover, as in the traditional banking sector, the boom was fostered by substantial inflows of foreign capital. This raises the question whether the crisis resilience the microfinance sector has shown in the past remains a characterizing feature of microfinance or whether the same risk factors associated with excessive credit growth lead - as in the traditional banking sector - to greater vulnerability. The findings indicate that microfinance markets with strong capital inflows, high credit growth rates and rapidly increasing competition experienced a substantial decrease in credit growth and deterioration of portfolio quality in the post-Lehman period. This is in line with the evidence found for the traditional banking sector in emerging markets and developing countries. The paper concludes that by becoming part of the global financial system, microfinance has lost one of the characteristics which distinguish it from traditional banking, namely its higher resilience towards crises in domestic and global financial markets.
Keywords: E44; G01; G21; 330; microfinance; crisis resilience; credit boom; financial crisis; Mikrofinanz; Kreditgeschäft; Bubbles; Finanzmarktkrise; Bankenkrise; Internationaler Finanzmarkt; Spillover-Effekt; Aufstrebende Märkte; Schwellenländer; Entwicklungsländer; USA